Improving Food and Nutritional Security of Rural Women: Action Study - K.G., Aparna Meenakshi; Krishnan I., Athira; K.V., Gayathri; V., Sithara Balan (Indian Journal of Extension Education, 2019)
The study was undertaken in Kudappanakunnu village of Thiruvananthapuram district in Kerala. Five case studies were done by analyzing their economic condition. The data were collected using questionnaire method. From the study it was found that majority of the respondents had medium level of knowledge on organic farming techniques. The women were provided with grow bags and vegetable seeds for improving their nutritional status. This initiative was introduced for improving their nutritional status along with income of the respondents. It was imperative that small initiative helped in improving nutritional status as well as improved waste disposal practices of the sampled women farmers.
Keywords: Food and Nutritional Security; Rural Community; Organic Farming